Efficient water disinfection against antibiotic-resistant bacteria by visible-light heterogeneous photo-Fenton-like process with atomically dispersed Cu on graphitic carbon nitride as the catalyst - Liu, Hang (2024)
Waterborne microbial contamination poses significant environmental and health risks. Photocatalytic heterogeneous Fenton and Fenton-like processes can offer efficient pathogen removal, with benefits in recycling, solid–liquid separation, and byproduct avoidance. However, their low reaction efficiency and slow kinetics for low-valence metal regeneration are limitations. This study addresses these challenges by incorporating atomically dispersed Cu onto graphitic carbon nitride (g-CN) as a single-atom catalyst (SAC). The Cu atoms are stabilized by pyridinic N atoms through coordination, forming Cu-N4 catalytic sites that enhance photogenerated charge carrier transfer. This leads to a more efficient synergistic photocatalytic-Fenton-like reaction, generating more hydroxyl radicals and achieving effective water disinfection. Results show a 7-log bacterial inactivation of antibiotic-resistant Acinetobacter baumannii within 8 min, surpassing prior photocatalytic-Fenton-like disinfection systems. Density functional theory calculations confirm improved hydrogen peroxide adsorption, electron transport, and electron-hole separation in the Cu-N4 structure. The catalyst's durability and stability were demonstrated through extensive cycling experiments, ion interference tests, and disinfection trials in various water matrices. Additionally, the Cu-SAC@CN catalyst, loaded onto a polytetrafluoroethylene membrane, achieved a 99% bacterial eradication rate within 20 min. This study provides valuable insights into the potential applications of heterogeneous photocatalytic-Fenton-like systems for efficient eradication of waterborne bacteria.